Abrupt changes in algal biomass of thousands of US lakes are related to climate and are more likely in low-disturbance watersheds - Patricia A. Soranno; Patrick J. Hanly; Katherine E. Webster; Tyler Wagner; Andrew McDonald; Arnab Shuvo; Erin M. Schliep; Kaitlin L. Reinl; Ian M. McCullough; Pang-Ning Tan; Noah R. Lottig; Kendra Spence Cheruvelil (Proceedings of the National Academy of Sciences, 2025)
Climate change is predicted to intensify lake algal blooms globally and result in regime shifts. However, observed increases in algal biomass do not consistently correlate with air temperature or precipitation, and evidence is lacking for a causal effect of climate or the nonlinear dynamics needed to demonstrate regime shifts. We modeled the causal effects of climate on annual lake chlorophyll (a measure of algal biomass) over 34 y for 24,452 lakes across broad ecoclimatic zones of the United States and evaluated the potential for regime shifts. We found that algal biomass was causally related to climate in 34% of lakes. In these cases, 71% exhibited abrupt but mostly temporary shifts as opposed to persistent changes, 13% had the potential for regime shifts. Climate was causally related to algal biomass in lakes experiencing all levels of human disturbance, but with different likelihood. Climate causality was most likely to be observed in lakes with minimal human disturbance and cooler summer temperatures that have increased over the 34 y studied. Climate causality was variable in lakes with low to moderate human disturbance, and least likely in lakes with high human disturbance, which may mask climate causality. Our results explain some of the previously observed heterogeneous climate responses of lake algal biomass globally and they can be used to predict future climate effects on lakes.